Panmen Get Own Road March - Joseph, Terry (Express)
Pan Trinbago decides to have its own Road March competition for steelpan. This decision comes on the heels of the disagreement between Pan Trinbago and the National Carnival Bands Association. Pan Trinbago's President Patrick Arnold said that the idea to organize this type of competition originated from Lord Kitchener whose calypso tributes to the steelpan are legendary.
Keywords: Pan Trinbago (Organization); Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago